The Role of the East Java Provincial Government on Export Import in Industry in East Java During the Covid-19 Pandemic - Pratama Septanoris; Yudi Sutrasna; Novky Asmoro (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Exports and imports have a very large role in various industries. At this time, the performance of exports and imports in Indonesia is getting better and continues to increase even during a pandemic. East Java is the second largest economic contributor in Java with a contribution of 25.01 percent after Jakarta. This study aims to examine how export and import in the industry in East Java can support national defense. The type of research that will be used by the author in this study is qualitative research presented descriptively. The results of this study indicate that the Provincial Government of East Java has made efforts to maintain export and import in East Java. The East Java government must continue to pay attention to future obstacles so that the industry in East Java is still able to compete in the global market.